Mechanisms of inter-individual variation in exercise performance at altitude - Carter, E. A. (The University of British Columbia, 2019)
Endurance athletes competing at altitude experience a significant decrement in performance as a result of the reduced partial pressure of oxygen. There is significant inter-individual variability in how altitude affects these athletes and the mechanism through which this decrement occurs. The ability to recognize one`s personal response to hypoxia and employ strategies (i.e. acclimatization) to mitigate this response is extremely useful to competitive athletes. For my dissertation, I attempted to identify some of the mechanisms that are responsible for the inter-individual variation in exercise performance at altitude. I conducted (i) an initial study on "fly-in fly-out" acclimatization to prepare for competition at altitude; (ii) a study comparing onset of intrapulmonary arteriovenous anastomoses (IPAVA) at rest with the decrement in exercise performance at altitude and the effects of the pulmonary vasodilator sildenafil on IPAVA recruitment; (iii) a mock competition study investigating the effects of sildenafil on exercise performance at altitude; and (iv) a meta-analysis of the effects of sildenafil on exercise performance at altitude. The most important findings of my dissertation are that (i) a 12-hour overnight exposure to hypoxia does not give any acclimatization benefit nor does it have any detrimental effect on a maximal exercise test; (ii) sildenafil does not affect IPAVA recruitment in hypoxia, nor does IPAVA onset appear related to exercise performance in hypoxia; (iii) sildenafil does not improve exercise performance in a 16.1 km cycling time-trial at a simulated altitude of 3,000 m; (iv) the decrement in exercise performance at altitude appears to be closely related to oxygen saturation; and (v) while sildenafil does appear to reduce pulmonary artery pressure, and increase cardiac output and oxygen saturation, it does not reliably improve performance. This dissertation demonstrates the wide variation in the decrement in exercise performance due to hypoxia, examining several of the predictors and moderators of exercise performance.